FRI0046 Anti-Carbamylated Protein Antibodies Precede the Onset of Symptoms of Rheumatoid Arthritis in A Swedish Biobank Cohort. (10th June 2014) - Brink, M.; Verheul, M.K.; Rönnelid, J.; Toes, R.E.; Klareskog, L.; Trouw, L.L.; Rantapää Dahlqvist, S.
Abstract : Background: Antibodies against citrullinated peptides of several specificities (ACPAs) have been found to predate the onset of symptoms of rheumatoid arthritis (RA) by years. The presence of a new auto-antibody system, anti-carbamylated protein (anti-CarP) antibodies has been identified in rheumatoid arthritis (RA) even predating the disease onset. Anti-CarP antibodies were associated with RA irrespectively of ACPA status. Objectives: The presence of anti-CarP antibodies was evaluated in samples from individuals who subsequently developed RA before symptoms of joint disease and also after disease onset. Methods: 223 individuals, with 423 samples, who were identified before onset of symptoms of RA (median 5.2years IQR 2.6 – 8.9 years), as donors to the Medical Biobank of Northern Sweden. 192 of them were also sampled at the time of diagnose, and 197 population controls were identified from the Medical Biobank for analysis of anti-CarP IgG antibodies with ELISA as previously described (1). All samples were also analysed for anti-CCP2 antibodies with ELISA (Euro-Diagnostica). Cut-off levels were identified by receiver operating characteristic (ROC) curves with 97% specificity for anti-CarP. Results: The concentration of anti-CarP was significantly increased in the pre-symptomatic individuals compared with controls (median (IQR) 44.0 (142.6) AU/mL vs. 7.9 (43) AU/mL, p<0.001) and increased significantly after disease onset to 198.9 (379.1) AU/mL. The sensitivity for anti-CarP antibodies in the pre-symptomatic individuals including all samples was 13.9% (95%CI 11-17.6%, ) as compared to 42.2% (95%CI 35.4-49.3, ) after RA was diagnosed. The concentration of antibodies increased significantly the closer to disease onset the sample was collected. Sensitivity, less than 3 years before symptom onset, was 18.6% (95%CI 12.8-26.3). 5.1% of the anti-CCP negative pre-symptomatic individuals were anti-CarP ab positive and 10.4% of the anti-CCP negative RA-patients were anti-CarP positive. The frequencies of anti-CCP antibodies was in the pre-sympomatic individuals 35.7% (95%CI 31.3-40.4) and 74.6% (95%CI 67.9-80.3) in the RA patients Conclusions: These results indicate that the anti-CarP antibodies could be involved in the pathogenesis of RA independent of anti-CCP antibodies References: Shi J, Knevel R, Suwannalai P, van der Linden MP, Janssen GMC, van Veelen PA, et al. Autoantibodies recognizing carbamylated proteins are present in sera of patients with rheumatoid arthritis and predict joint damage. Proc. Natl. Acad. Sci. U. S. A. 2011;108(42):17372-7. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4530